RGD‐modified dihydrolipoamide dehydrogenase as a molecular bridge for enhancing the adhesion of bone forming cells to titanium dioxide implant surfaces. Issue 3 (25th November 2018) - Dayan, Avraham; Lamed, Raphael; Benayahu, Dafna; Fleminger, Gideon
Abstract: Titanium and its alloys are widely used in dental‐ and orthopedic implants, the outer surface of which is often oxidized to titanium dioxide (TiO2 ). To achieve efficient osseointegration with bone‐forming cells, it is desirable to counter the formation of the soft fibrous tissue around the implant by creating strong and stable interactions between the implant surface and bone‐forming osteoblasts. To address this challenge, a bioactive coating had to be designed. Protein adsorption to TiO2 is well known in the literature, but it is mostly characterized by weak associations, rendering less efficient implant osseointegration. We have previously demonstrated the unique conjugation between the dihydrolipoamide dehydrogenase (DLDH) protein and TiO2 surfaces, based on specific coordinative bonding via Cys–His–Glu–Asp motif residues. To enhance cell binding to DLDH and facilitate osseointegration, DLDH was bioengineered to include Arg–Gly–Asp (RGD) moieties (DLDH RGD ). Coating TiO2 disks with DLDH RGD led to improved adherence of integrin‐expressing osteogenic MBA‐15 to the surface of the disks. Following the enhanced adsorption, higher proliferation rates of the adherent cells, as well as faster mineralization were observed, compared to controls. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 107A: 545–551, 2019.